2010
DOI: 10.4062/biomolther.2010.18.1.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines against Infectious Diseases and Cancer

Abstract: -Progress in the development of DNA vaccines and their delivery strategies has been made since their initial concept as a next generation vaccine. Since DNA vaccine includes non-infectious DNA parts of pathogens, it can't cause disease yet it closely mimic the natural process of infection and immune responses. Despite their early promising results of controlling infectious diseases and cancer in small animal models, DNA vaccines failed to display a level of immunogenicity required for combating these diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 151 publications
0
4
0
Order By: Relevance
“…Electroporation (EP), the administration of electrical pulses to muscle following DNA injection, has been shown to enhance the immunogenicity of DNA vaccines in a wide variety of small and large animal models (Han et al, 2010). The potential of EP delivery for clinical applications has been also suggested (Luxembourg et al, 2007;Bodles-Brakhop et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Electroporation (EP), the administration of electrical pulses to muscle following DNA injection, has been shown to enhance the immunogenicity of DNA vaccines in a wide variety of small and large animal models (Han et al, 2010). The potential of EP delivery for clinical applications has been also suggested (Luxembourg et al, 2007;Bodles-Brakhop et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…44 23 ). These preclinical studies demonstrated that antigen codon optimization, CD4+ T helper cell epitope domain conjugation, and antigen targeting to specific intracellular compartments might be promising strategies to augment cancer Ag-specific CTL responses and antitumor activity.…”
Section: Dna Manipulation and The Use Of Xenogeneic Antigensmentioning
confidence: 96%
“…Previously, our group demonstrated using a herpes simplex virus (HSV)-2 gD DNA vaccine model that the naked injection of gD DNA vaccines along with plasmid DNA encoding Th0-, Th1-, and Th2-type cytokines, chemokines and co-stimulatory molecules can modulate Ag-specific antibody and cellular responses, and enhance protective immunity against HSV-2 challenges (reviewed in 23 ). These data suggest that these immune stimulatory molecules could be useful as cancer vaccine adjuvants for enhancing Ag-specific CTL responses, which are required for cancer eradication.…”
Section: Co-injection Of Cytokines and Other Moleculesmentioning
confidence: 99%
“…DNA vaccines have become a promising alternative for the treatment and prevention of different infectious diseases [1][2][3], such as tuberculosis [4]. Typically, this kind of vaccine consists of a modified bacterial plasmid DNA coupled to a gene sequence that encodes a desired protein.…”
Section: Introductionmentioning
confidence: 99%